Addressing The Mental Health Needs of Non-Local University Students: Gaps and Recommendations - Ruth Kusumaning Ayu; Zefa Prada Amelia; Saurina Angelina; Hayu Astuti (Fast in Social Sciences, 2025)
Living away from home during university years presents both opportunities and emotional challenges for students. This study aims to explore the mental health experiences of students who reside far from their families while pursuing higher education. Using a qualitative descriptive approach, data were collected through semi-structured interviews with 15 students aged 18-22 years, purposively selected from various faculties. Thematic analysis revealed several recurring issues, including homesickness, social isolation, academic pressure, and limited access to mental health services. Many participants reported difficulties in adapting to independent living, especially when emotional support from family was unavailable. Students also expressed hesitation in utilizing available university counseling services due to stigma and lack of information. However, those who maintained regular communication with their families or developed peer support networks exhibited better emotional resilience. These findings suggest that emotional well-being is strongly connected to social relationships, living environment, and institutional support systems. The study recommends that universities implement proactive strategies such as emotional wellness workshops, inclusive peer networks, and improved promotion of mental health services. Strengthening mental health support is essential for enhancing both academic performance and the overall quality of life for students living away from home.